AB0778 Role of pet scan in the management of patients with takayasu arteritis. (23rd January 2014) - Sharma, V.; Nagaraj, S.; Mangat, G.; Balakrishnan, C.; Krishna, B.; Samant, R.
Abstract : Background: Takayasu's arteritis (TA) is the most common large vessel vasculitis in India 1 . The rarity of the disorder and the heterogeneous nature of its clinical presentation predisposes to late diagnosis and delayed treatment. Disease activity Assessment is challenging. Indian Takayasu Activity Score (ITAS) is developed to capture manifestations attributable to disease activity in the last 3 months 2 . 18F-fluorodeoxyglucose–positron emission tomography (FDG-PET) could play a role in the management of large-vessel vasculitis and has been reported to have high sensitivity and specificity for assessment of active TA 3 . Objectives: To evaluate the role of 18FDG-PET scanning in the management of patients of TA vis-a-vis Physician Global Assessment (PGA), ITAS 2010 score, ESR and other imaging studies. Methods: Prospective study wherein consecutive patients with TA diagnosed by conventional angiogram or MR angiogram attending Rheumatology clinic were enrolled. 18FDG-Whole body PET scan was performed at enrolment and repeated 3 or 6 monthly as per treating physician's decision. Relevant clinical data was collected at the baseline and during the periodic follow-up visits (every 3 months). The disease activity was assessed by PGA, ITAS and ESR in addition to the PET scan and the data was entered into a pre-approved proforma. Patients were followed up for a minimum of 6 months to a maximum of 2 years. Results: 28 patients had 52 PET scans. Clinical profile was similar to other Indian studies evaluated. PET was done twice in 18 patients, thrice in 6 patients. PET intensity showed a significant correlation with the disease activity as assessed by the PGA (r=0.406, P=0.0028), ITAS (r=.312, P=.011) and ESR (r=0.356, P=0.0103). Change in PET intensity showed a good correlation with the change in disease activity (P=0.038) at the 2nd PET but did not show significant correlation with change in disease activity (P=0.500) at the 3rd PET (small sample, n=6). Simultaneous MRA was done in 3 patients. The results in these 3 patients showed agreement in terms of vessel wall edema (MRA) and uptake intensity (PET). PET showed a sensitivity of 94.3% and 95.6% when compared to the clinical disease activity assessed with PGA and ITAS respectively, but the specificity was poor (71.4%, 62.5% respectively). Sensitivity and specificity with ESR was 89.4% and 55.4% respectively. d with PGA and ITAS respectively, but the specificity was poor (71.4%, 62.5% respectively). Sensitivity and specificity with ESR was 89.4% and 55.4% respectively. Conclusions: This study revealed a good correlation between FDG uptake and disease activity with a good sensitivity in assessing disease activity but low specificity. Other disadvantages with PET are radiation exposure, high cost and non-availability in majority of centers. PET scan should be used in those situations, where clinical scores and laboratory parameters do not provide adequate information about disease activity. References: Joshi VR, G Mittal. Vasculitis–Indian perspective. J Assoc Physicians India 2006;54(Suppl):12–14. Misra, R. et al. ITAS and DEI.TAK—scores for clinical disease activity and damage extent in Takayasu aorto-arteritis. Rheumatology 2008;47(Suppl.2):ii101. Andrews J, Mason JC. Takayasu's arteritis–recent advances in imaging offer promise. Rheumatology 2007;46(1):6-15. Disclosure of Interest: None Declared